Recent declines in HIV infections at Silom Community Clinic Bangkok, Thailand corresponding to HIV prevention scale up: An open cohort assessment 2005–2018 - Sarika Pattanasin; Frits van Griensven; Philip A. Mock; Wichuda Sukwicha; Santi Winaitham; Kesinee Satumay; Siobhan O’Connor; Andrew C. Hickey; Taweesap Siraprapasiri; Joseph V. Woodring; Pachara Sirivongrangson; Timothy H. Holtz; et al. (International Journal of Infectious Diseases, 2020)
Objectives: We assessed HIV-1 infection among men who have sex with men (MSM) attending Silom Community Clinic (SCC) in Bangkok, Thailand from 2005 to 2018. Since 2014, Thailand increased implementation of HIV prevention strategies including pre-exposure prophylaxis and Treatment as Prevention. Methods: MSM attending SCC were tested for HIV using rapid tests. We assessed trends in HIV prevalence, incidence and compared incidence before and after 2014. Results: From 2005 to 2018, 14,034 clients attended SCC for HIV testing. The HIV prevalence increased from 19.2% in 2005–2006 to 34–0% in 2010, remained stable until 2016 and decreased to 17.2% in 2018 (p < 0.0001). The HIV incidence was 4.1 per 100 person-years (PY), with an inverted U-shape trend and a peak in 2009 (p < 0.0001). Incidence among young MSM aged 13–21 years remained high at 10.0 per 100 PY. Among those aged 22–29 years, lower incidence was found from Q 3 2016, with a relative risk reduction of 46.2% (p < 0.001); and a similar reduction among those aged ≥30 years from Q4 2014, corresponding to scale up of HIV prevention strategies. Conclusion: We found a decline in HIV infection among Thai MSM. However, incidence remained high among young MSM.